The importance of specific exercise therapy in pediatric oncology - Bianca Celine Schmidli; Céline Hammadou; Christina Schindera; Nicolas von der Weid; Uta Tacke; Oliver Faude; Sarah Koch; Fiona Streckmann (Current Issues in Sport Science)
Introduction Modern therapy has improved survival for children with cancer. However, treatment has unintended consequences. More and more studies are showing that children have persisting motor and sensory dysfunctions, such as loss of sensation, numbness, pain, absent reflexes as well as loss of balance control. Developmental milestones such as walking, running, jumping or climbing are delayed which negatively impacts their quality of life and social reintegration (Bjornard et al. 2018). Consequently, survivors are less inclined to participate in physical education at school and experience difficulties when engaging in sport activities with their peers. The beneficial effects of movement interventions have been documented in numerous studies. However, despite this potential, the promotion of physical activity (PA) within pediatric oncology is still a largely overlooked area of practice. The international Pediatric Oncology Exercise Guidelines (iPOEG) highlight PA and exercise as safe, beneficial and recommended for all children and adolescents with cancer (Wurz et al. 2021).